KEMAMPUAN PROBLEM-SOLVING MATEMATIS SISWA SMA DALAM MENYELESAIKAN PERMASALAHAN MATERI FUNGSI - Ramadhani, Delia Adinda; Hakim, Dori Lukman (IKIP Siliwangi, 2021)
Mathematical problem-solving ability is part of the main goal of learning mathematics. This study aims to analyze the problem-solving ability of high school students in solving problems with function material. So get a description of students in understanding the problem, devise a plan, carry out the plan, and look back in solving problems. This research is qualitative research using descriptive method. The study conducted on the tenth grade students of SMA Negeri 2 Telukjambe Timur, Karawang Regency. The instrument consists of solving the problem of function material which was adopted from the teaching materials of the 2017 revised edition of the curriculum compulsory textbook. The data analysis technique carried out consisted of three stages, namely analyzing the result of students' answers, presenting data from the analysis, and making conclusions from the results of research on students' mathematical problem-solving abilities.The result of this article provides an overview of problem-solving abilities in solving functional problems carried out by high school students related to mathematical problems.